Shackles, Collars, and Chains: Exposing the treatment of enslaved black women during the Middle Passage and as part of the archaeological record (1700-1886) - Dwyer, Kelsey (East Carolina University, 2021)
This thesis examines and argues that the shipboard narratives and material culture related to black enslaved women from 1700 through 1886 further illuminates gendered experiences. The study analyses the role of these African women through a maritime and archaeological lens, assessing the seventeenth-century slave ship artifact assemblages of Henrietta Marie and Whydah shipwrecks as case studies, in addition to historical illustrations of slave ships Brookes and Vigilante. Furthermore, it explores female enslavement and ways in which African enslaved women impacted the history of the Caribbean, with specific attention to the relationships between white men and black enslaved women, resulting in the formation of new ethnic identities and social structures associated with their mixed-heritage or "mulatto" children. Sources like artwork and ethno-historical accounts of mulatto children in areas of the Caribbean and the role of African enslaved women's unique provides insights into social dynamics and cultural markers of modern populations.
Keywords: slavery; gender-studies; shipwreck; Women slaves--History; Caribbean Area--History; Slave ships; Henrietta Marie (Ship); Whidah (Ship); Brookes (Ship); Vigilante (Ship)